The status of muslim women under the muslim law in federal territory / Aliza Yahya - Yahya, Aliza (Faculty of Law, 1986)
This book had been prepared in partial fulfillment of the Diploma in Law Course. It is hoped that it will serve as a useful reading for students of Muslim Family Law and every muslim woman. A study on the status of muslim women, is necessary, in order to let the muslim women know their rights during their marriage and if the marriage have been dissolved, their rights after divorce. Under Muslim Family Law, every woman has many rights bestowed upon her before or upon dissolution of a marriage. The Islamic marriage provisions apply equally to men and women. If celibacy is not recommended for men than it is not recommended for women. Marriage is the natural course for both. This book is to highlight the status of muslim women, for it is known fact that not all women are aware of their rights. There are some who,due to the lack of education, poverty and other factors are still igrevant of their full rights under Islam. With the increasing number of divorces in the Federal Territory, women should be more alert to their rights available under Muslim Family Law, so that they will not be much oppressed and taken for